Novel approaches to the stratified management of knee osteoarthritis - Fuggle, Nicholas R.; Chapurlat, Roland; Laslop, Andrea; Al-Daghri, Nasser; Alokail, Majed; Thiyagarajan, Jotheeswaran Amuthavalli; Balkowiec-Iskra, Ewa; Berenbaum, Francis; Bemden, Angie Botto van; Borg, John Joseph; Bruyère, Olivier; Burlet, Nansa; et al. (Nature Reviews Rheumatology, 2025)
Knee osteoarthritis is a highly prevalent whole-joint disease that is associated with substantial morbidity. If step changes are to be made in the management of knee osteoarthritis, novel patient stratification approaches are needed to identify the most effective treatment for individual patients. Numerous methods for stratifying patients with knee osteoarthritis can be employed; clinical presentation, including co-morbidity and pain phenotype, can influence treatment decisions, and there is a rich history of imaging biomarker use, both from conventional radiographs and, since its development, via MRI, in identifying patients at risk of disease progression, and the latter facilitates the detection of synovitis. The development of novel biochemical biomarkers and the rapid growth of ‘-omics’ technologies provide fresh opportunities to deploy these advances in the stratification of patients with knee osteoarthritis. The health economic landscape in this area is developing, and scoping work has highlighted the need for further studies.
Publisher Copyright: © Springer Nature Limited 2025.